(untitled) (Ameghiniana, 2013)
SOME CARBONIFEROUS MIOSPORES FROM AGUA COLORADA FORMATION,LA RIOJA PROVINCE.- A palynologic study of several samples collected. at a locality situated OD the eastern flank of the Sierra de Famatina is made. The miospores are found in carbonaceous claystones that belong to the, Agua Colorada Formation. Ten species are described, corresponding to the genera Punctatisporites, Anapiculatisporites, Apiculiretusispora , Raistrickia , Dictyotriletes, Ahrensisporites y Tetraporina . Also, some monosaccate pollen grains are present; they were not determined because they lack the central body. The first mention oí Ahrensisporites cristatus is significative; thís species has been recorded so far in Australian sequences, probably of the same age. The presence of several species in common with the known associations from Malanzán - Loma Larga and Pircas (= Tambillos river) within the Paganzo Basin, is also noted.